Governance fragmentation and accountability vacuum in palm oil transportation: Evidence from a rural village in Indonesia - Efendi, Hartatik; Muradi, Muradi; Sagita, Novie Indrawati (Universitas Muhammadiyah Malang, 2026)
Palm oil transportation in rural Indonesia generates significant environmental and social impacts that extend beyond cultivation-phase concerns. In Telaga Arum Village, North Kayong Regency, West Kalimantan, intensive truck traffic has degraded village roads, disrupted drainage systems, and constrained community mobility. This study examines how governance arrangements shape the management of these impacts at the village level. Using a qualitative case study design, data were collected over a 14-day field period (January–February 2026) through semi-structured interviews with twelve key informants representing village government, district authorities, palm oil companies, and community members, complemented by field observation and document analysis. Thematic analysis identifies four recurring governance patterns: (1) absence of binding accountability mechanisms for infrastructure maintenance, evidenced by repeated but unanswered formal repair requests; (2) community participation limited to deliberation forums without documented action plans or follow-up authority; (3) restricted transparency regarding operational agreements between companies and government; and (4) unpredictable intervention patterns driven by social or political pressure rather than stable regulatory frameworks. These findings demonstrate that infrastructure degradation is not solely a technical issue but reflects an “accountability vacuum,” defined as a governance condition in which multiple actors are formally present but none hold enforceable responsibility due to fragmented authority and jurisdictional ambiguity. This concept advances environmental governance analysis by distinguishing situations of distributed but non-binding responsibility from more general forms of weak enforcement or coordination failure. The study concludes that improving governance requires institutional reforms that clarify intergovernmental responsibilities, establish binding corporate obligations for the use of public infrastructure, and strengthen participatory mechanisms by linking community input to decision-making authority. The findings contribute to broader debates on local environmental governance by showing how global commodity logistics produce localized governance gaps in rural contexts. Aktivitas transportasi kelapa sawit di wilayah perdesaan Indonesia menimbulkan dampak lingkungan dan sosial yang signifikan yang melampaui isu pada tahap budidaya. Di Desa Telaga Arum, Kabupaten Kayong Utara, Kalimantan Barat, intensitas lalu lintas truk yang tinggi menyebabkan kerusakan jalan desa, gangguan sistem drainase, serta pembatasan mobilitas masyarakat. Penelitian ini bertujuan untuk menganalisis bagaimana tata kelola memengaruhi penanganan dampak tersebut di tingkat desa. Penelitian ini menggunakan pendekatan studi kasus kualitatif. Data dikumpulkan selama periode lapangan 14 hari (Januari–Februari 2026) melalui wawancara semi-terstruktur dengan dua belas informan kunci yang mewakili pemerintah desa, pemerintah daerah, perusahaan kelapa sawit, dan masyarakat, serta dilengkapi dengan observasi lapangan dan analisis dokumen. Analisis tematik mengidentifikasi empat pola utama tata kelola: (1) ketiadaan mekanisme akuntabilitas yang mengikat dalam pemeliharaan infrastruktur, yang ditunjukkan oleh pengajuan permintaan perbaikan yang berulang namun tanpa respons formal; (2) partisipasi masyarakat yang terbatas pada forum musyawarah tanpa rencana aksi dan tindak lanjut yang mengikat; (3) keterbatasan transparansi terkait kesepakatan operasional antara pemerintah dan perusahaan; serta (4) pola intervensi yang tidak dapat diprediksi dan lebih dipengaruhi oleh tekanan sosial atau politik daripada kerangka regulasi yang stabil. Temuan ini menunjukkan bahwa degradasi infrastruktur tidak semata-mata disebabkan oleh faktor teknis, melainkan mencerminkan adanya “kekosongan akuntabilitas” (accountability vacuum), yaitu kondisi tata kelola di mana berbagai aktor secara formal terlibat, tetapi tidak ada pihak yang memiliki tanggung jawab yang mengikat akibat fragmentasi kewenangan dan ambiguitas yurisdiksi. Konsep ini memperluas analisis tata kelola lingkungan dengan membedakan kondisi tanggung jawab yang tersebar namun tidak mengikat dari bentuk kegagalan tata kelola lainnya seperti lemahnya penegakan atau kegagalan koordinasi. Penelitian ini menyimpulkan bahwa perbaikan tata kelola memerlukan reformasi kelembagaan yang menegaskan pembagian kewenangan antar level pemerintahan, menetapkan kewajiban perusahaan yang mengikat dalam penggunaan infrastruktur publik, serta memperkuat mekanisme partisipasi dengan menghubungkan aspirasi masyarakat dengan otoritas pengambilan keputusan. Studi ini berkontribusi pada pengembangan kajian tata kelola lingkungan lokal dengan menunjukkan bagaimana rantai pasok komoditas global menghasilkan kesenjangan tata kelola di tingkat perdesaan.